2011
DOI: 10.1200/jco.2011.29.4_suppl.87
|View full text |Cite
|
Sign up to set email alerts
|

Randomized phase II study of nimotuzumab, an anti-EGFR antibody, plus irinotecan in patients with 5-fluorouracil–based regimen-refractory advanced or recurrent gastric cancer in Korea and Japan: Preliminary results.

Abstract: 87 Background: Nimotuzumab is a humanized IgG1 anti-EGFR monoclonal antibody. In previous studies, nimotuzumab has demonstrated efficacy associated with an absence of severe skin toxicity, commonly caused by other EGFR-targeting therapies. Methods: This is a Korea and Japan collaborative, multi-center, randomized, open-label study of nimotuzumab (400 mg, IV q1 week) plus irinotecan (150 mg/m2 IV q2 weeks) (N+I) versus irinotecan (I) in patients with advanced or metastatic gastric cancer refractory to 5-fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…The ToGA (Trastuzumab for Gastric Cancer) trial has shown that trastuzumab improves the survival of patients with HER2 protein-overexpressing and/or HER2 geneamplifying advanced gastric cancer [5]. Although the addition of cetuximab or panitumumab to chemotherapy in non-molecularly selected gastric cancer patients did not improve survival [6,7], a phase 2 study has shown a possible improvement in the survival of the patient subset with high EGFR expression who were treated with nimotuzumab, a humanized monoclonal antibody to EGFR [8]. At present, a phase 3 nimotuzumab trial (ENRICH study) in patients with EGFR-overexpressing advanced gastric and gastroesophageal junction cancer is ongoing.…”
Section: Introductionmentioning
confidence: 99%
“…The ToGA (Trastuzumab for Gastric Cancer) trial has shown that trastuzumab improves the survival of patients with HER2 protein-overexpressing and/or HER2 geneamplifying advanced gastric cancer [5]. Although the addition of cetuximab or panitumumab to chemotherapy in non-molecularly selected gastric cancer patients did not improve survival [6,7], a phase 2 study has shown a possible improvement in the survival of the patient subset with high EGFR expression who were treated with nimotuzumab, a humanized monoclonal antibody to EGFR [8]. At present, a phase 3 nimotuzumab trial (ENRICH study) in patients with EGFR-overexpressing advanced gastric and gastroesophageal junction cancer is ongoing.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] Recently, RCTs investigated the efficacy of the targeted therapy alone or in combination with chemotherapy, but results were mostly unsatisfactory. [25][26][27][28][29][30][31][32][33][34][35][36][37][38] While several RCTs demonstrated an improvement in terms of response rate (RR), and progression free survival (PFS) only one study reported a significant increase in terms of OS in a selected subgroup of patients in front-line treatment. 25 In that trial, patients were selected according to HER2 status (resulted to be overexpressed in 16-34% of patients with intestinal type and 2-7% of diffuse aGC), and subsequently treated with trastuzumab plus standard chemotherapy with a significant 2.7 months advantage in OS.…”
Section: Conventional Treatmentmentioning
confidence: 99%
“…[25][26][27][28][29][30][31][32][33][34][35][36][37]44,[51][52][53][54][55][56][57][58][59] The TYTAN trial missed data about PFS. One trial missed results about OS.…”
Section: Studies Selectionmentioning
confidence: 99%
“…The results of a recent ToGA trial revealed that the anti-HER2 antibody trastuzumab improves the survival of patients with HER2-positive advanced gastric cancer [2]. The results of other studies suggest the potential efficacy of targeted therapy against gene alterations in gastric cancers [8][9][10], and several other therapeutic drugs against these RTKs, including EGFR, are currently under investigation [11].…”
Section: Introductionmentioning
confidence: 99%
“…The recent REAL3 (panitumumab) [19] and EXPAND (cetuximab) [20] randomized controlled phase III trials failed to demonstrate the efficacy of the anti-EGFR monoclonal antibodies for treating gastric cancer, presumably because precise patient inclusion criteria were not set for the trials. Several studies suggest that EGFR overexpression or gene amplification may serve as a potential biomarker for the efficacies of anti-EGFR therapies in gastric cancer [9,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%